VISUAL IMPROVEMENT FOLLOWING THE REMOVAL OF CHRONIC ORBITAL CAVERNOUS HEMANGIOMA - Raisha Pratiwi Indrawati; M. Rinaldi Dahlan (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Orbital cavernous hemangioma is a benign, well-defined vascular lesion, located mainly in the intraconal space. Surgical treatment is indicated in symptomatic cases, such as proptosis or visual disturbance. This study aims to report the visual improvement of the successfully-managed chronic orbital cavernous hemangioma. Case Report: A 51-year-old man came to Cicendo Eye Hospital with chief complaint of protrusion of the right eye for seventeen years, accompanied by blurred vision two years earlier. Ophthalmological examination revealed decreased visual acuity, together with ocular movement restriction and relative afferent pupillary defect. Computed tomography (CT) scan showed a retrobulbar mass, attached to the lateral and medial rectus muscle, and shifting the optic nerve superiorly. The tumor was removed through inferior anterior orbitotomy with a transconjunctival incision, and the histopathological finding revealed a cavernous hemangioma. Follow-up examination showed improvement in the patient's condition, measured by no protrusion remaining and the achievement of best-corrected visual acuity (BCVA) of 1.0. Discussion: In the case of a benign intraorbital tumor, the orbitotomy approach should be best selected based on its anatomical location and involvement of adjacent structures. Despite the size of the tumor, chronic duration, and disturbing manifestation, improvement of visual acuity and structural appearance could be achieved if the tumor is removed correctly and the adjacent structure has not been severely damaged. Conclusion: Cavernous hemangioma is a benign lesion in which surgical treatment is indicated in symptomatic cases. The right approach of orbitotomy is needed to give a good outcome anatomically and functionally.